Edukasi kesehatan pencegahan Covid-19 kepada masyarakat tepian Sungai Kuantan - Suyanto Suyanto; Zulkarnaini Zulkarnaini (Unri Conference Series: Community Engagement, 2020)
Covid-19 has infected people not only in urban areas but also in rural areas. Prevention efforts have been carried out massively by various parties in the form of health messages, but the delivery of these messages has not been able to touch people who live far from the capital. For this reason, there should be an effort to socialize the prevention of Covid-19 diseases, such as for people living on the banks of the Kuantan River. The activity carried out by academics at the University of Riau together with Kukerta students is a real effort to prevent the spread of this disease in the community.